PENGARUH BAHAN BAKU DAN TEKNIK PEWARNAAN TERHADAP VARIABEL KEUANGAN SOUVENIR BARONG PADA BTIKK - I Nyoman Normal (Forum Manajemen STIMI Handayani Denpasar, 2021)
The aims of this research was to determine the effect of changes in raw materials and coloring techniques on the financial variables of biscuit-baked barong souvenirs at BTIKK in 2019. This research method is descriptive quantitative, which data sources are internal and external, both primary and secondary. The analysis techniques are: a standard cost system based on full costing to calculate the cost of goods manufactured, cost-plus pricing to calculate the selling price, and the operating profit margin method to calculate profitability. The results showed that the change in raw material from CN-17 cast mass to BPN-01 cast mass and the coloring technique from underglaze to onglaze could increase financial variables (cost of goods manufactured, selling price, and operating profit margin) of biscuit-baked barong souvenir (l30,0 - w10,0 - h25,0). The effect on the cost of goods manufactured of barong souvenir made of CN-17 mass raw material for underglaze staining, BPN-01 cast mass raw material under underglaze staining, CN-17 cast mass raw material onglaze staining, and BPN-01 cast mass raw material for onglaze staining are increasing respectively 548.76%, 553.64%, 563.88%, and 568.67% respectively compared to biscuit-baked barong souvenir, because changes in raw materials and / or coloring techniques change the composition and types of raw materials which cost more expensive, time processing takes longer, the cost of colour material is more expensive, and the frequency of burning is increased by two or three times.